2019
DOI: 10.1002/ppul.24366
|View full text |Cite
|
Sign up to set email alerts
|

Gene modifiers of cystic fibrosis lung disease: A systematic review

Abstract: Background Lung disease is the major source of morbidity and mortality in cystic fibrosis (CF), with large variability in severity between patients. Although accurate prediction of lung disease severity would be extremely useful, no robust methods exist. Twin and sibling studies have highlighted the importance of non‐cystic fibrosis transmembrane conductance regulator (CFTR) genes in determining lung disease severity but how these impact on the severity in CF remains unclear. Methods A systematic review was un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 109 publications
(187 reference statements)
0
22
0
Order By: Relevance
“…This observation has led to the hypothesis that additional genetic loci likely contribute to pathophysiology of CF disease. Several studies have identified polymorphisms in genes related to innate immune function that appear to alter CF disease severity, including MUC4/MUC20, SLC9A3, SLC26A9, HLA Class II, AGTR2/SLC6A14, IFRD1, DCTN4, and EHF/APIP [4].…”
Section: Introductionmentioning
confidence: 99%
“…This observation has led to the hypothesis that additional genetic loci likely contribute to pathophysiology of CF disease. Several studies have identified polymorphisms in genes related to innate immune function that appear to alter CF disease severity, including MUC4/MUC20, SLC9A3, SLC26A9, HLA Class II, AGTR2/SLC6A14, IFRD1, DCTN4, and EHF/APIP [4].…”
Section: Introductionmentioning
confidence: 99%
“…It has been well known that the severity of CF lung disease varies dramatically even in patients with identical CFTR genotypes, in which genetic factors play an important role. [21][22][23] A review collected recent efforts aiming at identifying non-CFTR modifier genes for lung disease severity in cystic fibrosis. [21] Genotyping of reported modifier loci showed that patient 6 − 1 carried several risk alleles in the TGFB1, MUC4/MUC20 and HLA Ⅱ genes but patient 6 − 2 did not; the rest loci turned out to be the same for the siblings (Table S1).…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23] A review collected recent efforts aiming at identifying non-CFTR modifier genes for lung disease severity in cystic fibrosis. [21] Genotyping of reported modifier loci showed that patient 6 − 1 carried several risk alleles in the TGFB1, MUC4/MUC20 and HLA Ⅱ genes but patient 6 − 2 did not; the rest loci turned out to be the same for the siblings (Table S1). The TGFB1 codon 10 CC genotype (rs1800470) detected in patient 6 − 1 was reported to be related to severe lung function with an odds ratio of about 2.2.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the identification of the CFTR gene and the growing mutation database, establishing a correlation between CF genotype and clinical phenotype remains difficult, considering the vastly different disease courses between patients, even between twin siblings sharing the same CFTR mutations ( Kerem et al, 1990 ; Mekus et al, 2000 ). Genome-wide association studies with large patient cohorts have identified genetic variants of specific loci associated with disease severity, called CF modifier genes, that contribute to phenotypic variability [see recent reviews ( Lim et al, 2018 ; Shanthikumar et al, 2019 )]. Among the proteins encoded by the CF modifier genes, some have direct protein-protein interaction with CFTR and/or are involved in immune response ( Tugores et al, 2001 ; Wright et al, 2011 ; Stanke et al, 2014 ; Corvol et al, 2015 ).…”
Section: Inflammation In Cf Airwaymentioning
confidence: 99%